On ASEM and the Cartography of Asia, Africa and Europe - Korhonen, Pekka (AEI Insights, 2021)
The ASEM has been growing steadily in size and scope since its inception in 1996, and will probably continue to do so in the future. This article tries to map both the history of the concepts for depicting the classical continents and their very flexible boundaries, as well as a possible future course for ASEM from a cartographic point of view, especially in regard to the importance of and interest in Africa that most current ASEM members are showing. This is also considered as one of the future recommendable directions of the expansion of ASEM.